A new species of carebara from the philippines with notes and comments on the systematics of the carebara genus group (hymenoptera: formicidae: myrmicinae) (2010)
A new myrmicine ant species from the Philippines, Carebara alperti n. sp., isdescribed with taxonomic notes about the genus. The new species is congruent withthe genus defi nition proposed recently by Fernández (2004). The myrmicine ant genusParvimyrma is synonymized under Carebara (n. syn.), and the new combinationCarebara sangi (Eguchi and amp; Bui 2007) is proposed. Reinterpretation of Carebaravilliersi, originally described in the genus Nimbamyrma, suggests that Pheidologetonshould probably be synonymized within Carebara. A synoptic sketch of the systematicof the Carebara genus group is provided to show probable phylogenetics relationships.Carebara arabara is proposed as a new name for Carebara striata Fernández,2004:228.